Free surface flow over a triangular depression - Merzougui, A; Laiadi, A (TWMS journal of applied and engineering mathematics, 2014)
Two-dimensional steady free-surface ows over an obstacle is considered. The fluid is assumed to be inviscid, incompressible and the flow is irrotational. Both gravity and surface tension are included in the dynamic boundary conditions. Far upstream, the flow is assumed to be uniform. Triangular obstruction is located at the channel bottom. In this paper, the fully nonlinear problem is formulated by using a boundary integral equation technique. The resulting integro-di erential equations are solved iteratively by using Newton's method. When surface tension and gravity are included, there are two additional parameters in the problem known as the Weber number and Froude number. Finally, solution diagrams for all flow regimes are presented.